Incorporation of Chemically Modified and Radiation-sterilized Cancellous Bone Allografts - Roe, S. C.; Milthorpe, B. K.; Schindhelm, K.; Howlett, C. R. (Veterinary and Comparative Orthopaedics and Traumatology, 1995)
The effect of lipid extraction, partial decalcification, iodoacetate treatment and glutaraldehyde (GA) cross-linking on incorporation of radiation-sterilized cancellous bone allografts was compared to unmodified radiation-sterilized cancellous bone allografts and autogenous cancellous bone grafts in a cortical defect model in sheep tibia. Incorporation of the grafts was compared radiographically and histologically 56 days after implantation. The quantity and depth of extension of fluorescent label into the graft were evaluated from photomicrographs. GA cross-linked allografts were more poorly incorporated and had the least penetration of tetracycline-labelled bone. All other allografts were incorporated similarly to the autografts except that tetracycline- labelled bone was present to a greater depth in the autografts. The minimal differences between allografts and autografts may be explained by a reduction of the immunogenicity of all allografts by freezing and by radiation sterilization. GA cross-linking prevented resorption of bone. Ingrowth may have been inhibited by residual GA.Chemically modified cancellous bone allografts were implanted in sheep tibia. Their incorporation was compaed to unmodified allografts and autografts using microradiographs and histological evaluation. Glutaraldehyde cross-linked allografts were minimally resorbed and had little bone ingrowth. All other allografts were well incorporated. Bone ingrowth into autografts was more rapid but extent of incorporation after 56 days was similar to allografts.
Keywords: Cancellous bone; allograft; chemical modification; incorporation